1996
DOI: 10.1074/jbc.271.51.32519
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Ethyl Esters, Nonoxidative Metabolites of Ethanol, Accelerate the Kinetics of Activation of the Human Brain Delayed Rectifier K+ Channel, Kv1.1

Abstract: Herein we demonstrate that the major metabolites of ethanol in neural tissues, fatty acid ethyl esters, dramatically accelerate the kinetics of the voltage-induced activation of the human brain delayed rectifier potassium channel, Kv1.1. Specifically, the external application of ethyl oleate (20 M) to Sf9 cells expressing the recombinant Kv1.1 channel resulted in a decrease in the rise times of the macroscopic current (e.g. from 51.7 ؎ 13.1 to 12.8 ؎ 3.0 ms at 0 mV for 10 -90% rise times) and a 10-mV hyperpola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Nicotinic receptors are also modulated by ethanol (Fröhlich et al 1994;Nagata et al 1996). Finally, pharmacological effects of non-oxidative metabolites of ethanol in the brain, such as fatty acid ethyl esters (Gubitosi-Klug and Gross 1996) and phosphatidylethanol (Gustavsson, 1995) must be considered. Further studies are required to elucidate the molecular mechanisms of ethanol's effects on the septohippocampal pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Nicotinic receptors are also modulated by ethanol (Fröhlich et al 1994;Nagata et al 1996). Finally, pharmacological effects of non-oxidative metabolites of ethanol in the brain, such as fatty acid ethyl esters (Gubitosi-Klug and Gross 1996) and phosphatidylethanol (Gustavsson, 1995) must be considered. Further studies are required to elucidate the molecular mechanisms of ethanol's effects on the septohippocampal pathway.…”
Section: Resultsmentioning
confidence: 99%
“…However, linoleic acid also affects activation gating by causing a leftshift in the activation curve. Arachidonic acid, a lipid signaling molecule arising from phospholipid metabolism, induces fast inactivation of otherwise non-inactivating Kv channels (Kv1.1 and 3.1) [15] but it also accelerates activation of Kv1.1 [16]. There are other compounds, namely ginsenoside Rg 3 and verapamil, which appear to block Kv channels by accelerating C-type inactivation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…channels. Other compounds which have been reported to modify (accelerate) C-type inactivation but also somewhat affect activation gating behaviors include KN-93, linoleic acid, and arachidonic acid [13][14][15][16]. We previously reported that HMJ-53A blocks Kv channels extracellularly by accelerating the closing of the inactivation gate [17].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell voltage clamp recordings of Sf9 cells were performed by using standard techniques as described (28)(29)(30)(31). Sf9 cells lack any depolarization-induced current and, therefore, provide a null background for determination of voltage-activated potassium channels (26,28).…”
Section: Methodsmentioning
confidence: 99%